Criminological Analysis of Child Sexual Violence in the Family: An Indonesian Case Study Based on Routine Activity Theory - Saefudin, Yusuf; Kinanthya Anugrahing , Gusti; Nesya Rizky, Silviana; Zahra Aliyah Khoirun, Nisa (Kosmik Hukum, 2025)
This research aims to analyze the phenomenon of sexual violence against children committed by individuals from the immediate environment, particularly within the family, using a criminological approach through Routine Activity Theory (RAT). This approach focuses on understanding how criminal opportunities are shaped by the interaction between motivated offenders, vulnerable targets, and the absence of effective guardianship. The method employed is a literature review, utilizing secondary data such as laws and regulations, official documents, state agency reports, and relevant academic literature. The analytical technique applied is descriptive-qualitative and prescriptive analysis, aiming to identify criminogenic factors and power dynamics that enable sexual violence to occur within private spheres. The findings indicate that perpetrators typically possess emotional and structural access to victims and exploit relational inequalities to commit acts of sexual abuse. Weak social control and limited public literacy regarding child protection further increase the opportunity for such crimes to take place. Therefore, enhancing the capacity of community-based supervision and strengthening the legal protection system are essential for effective prevention. This study is significant as it offers a criminological lens that moves beyond psychological or juridical approaches by integrating Routine Activity Theory to explain the structural conditions that facilitate child sexual abuse, especially within familial contexts in Indonesia.